2008
DOI: 10.1073/pnas.0807413105
|View full text |Cite
|
Sign up to set email alerts
|

A placenta-specific receptor for the fusogenic, endogenous retrovirus-derived, human syncytin-2

Abstract: Syncytin-2 is an envelope gene from the human endogenous retrovirus FRD (HERV-FRD) co-opted by an ancestral primate host, conserved in evolution over >40 Myr, specifically expressed in the placenta, and with a cell-cell fusogenic activity likely contributing to placenta morphogenesis. Here, using the GeneBridge4 human/Chinese hamster radiation hybrid panel, we mapped and identified the human receptor for syncytin-2. This receptor-namely Major Facilitator Superfamily Domain Containing 2 (MFSD2)-belongs to a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(168 citation statements)
references
References 36 publications
4
156
0
4
Order By: Relevance
“…Both env genes display placenta-specific expression and induce syncytium formation when introduced into cultured cells (figure 2c), which led to their designation as syncytin-1 and syncytin-2, respectively. Each protein binds a distinct receptor: syncytin-1 interacts with the neutral amino acid transporter ASCT2 [36] and syncytin-2 with the multipass transmembrane protein MFSD2 [39]. Comparative analysis of the syntenic regions within the genomes from various species revealed that the syncytin-1 gene entered the genome of primates before the separation of Hominoids from Old World monkeys, being conserved only in Hominoids [40], whereas syncytin-2 was found to be conserved in the genome of all primates, except prosimians [38].…”
Section: Human Endogenous Retrovirus Env Genesmentioning
confidence: 99%
“…Both env genes display placenta-specific expression and induce syncytium formation when introduced into cultured cells (figure 2c), which led to their designation as syncytin-1 and syncytin-2, respectively. Each protein binds a distinct receptor: syncytin-1 interacts with the neutral amino acid transporter ASCT2 [36] and syncytin-2 with the multipass transmembrane protein MFSD2 [39]. Comparative analysis of the syntenic regions within the genomes from various species revealed that the syncytin-1 gene entered the genome of primates before the separation of Hominoids from Old World monkeys, being conserved only in Hominoids [40], whereas syncytin-2 was found to be conserved in the genome of all primates, except prosimians [38].…”
Section: Human Endogenous Retrovirus Env Genesmentioning
confidence: 99%
“…Puis la sous-unité d'ancrage transmembranaire (TM) induit la fusion entre la membrane du virus et la membrane plasmique de la cellule cible grâce à un peptide de fusion ( Figure 1A et 1B Figure 1D), d'où leur appellation de syncytine-1 et syncytine-2. Les deux protéines interagissent avec des récepteurs distincts : le récepteur des rétrovirus de type D (RDR/ASCT-2, pour sodium-dependent neutral amino acid transporter type 2) pour la syncytine-1 [10] et une protéine transmembranaire MFSD2 (major facilitator superfamily domain containing 2A) pour la syncytine-2 [13]. Des analyses génomiques comparatives ont révélé que la syncytine-1 est apparue dans le génome primate après la spéciation Hominoïdae/singes de l'Ancien Monde, il y a environ 25 millions d'années (Ma) [14].…”
Section: Rôles De La Protéine D'enveloppe Rétrovirale : Du Cycle Viraunclassified
“…La syncytine-1, exprimée de manière peu spécifique dans le placenta, est détectée dans tous les trophoblastes des lignages villeux (cytotrophoblastes et syncytiotrophoblaste) et extravilleux [19,20] ( Figure 2B). En revanche, la syncytine-2 est détectée dans une fraction des cytotrophoblastes des villosités [21] et son récepteur, MFSD2, est exprimé dans le syncytiotrophoblaste [13] ( Figure 2B). L'expression très régulée des deux partenaires syncytine-2/MFSD2 dans des types cellulaires [21,37]) et du récepteur de la syncytine-2, MFSD2 (expériences d'hybridation in situ sur coupes de placenta du 3 e trimestre [13]), dans le placenta humain.…”
Section: Implication Des Syncytines Dans Le Développement Placentaireunclassified
See 2 more Smart Citations